Interference competition between ants (Hymenoptera: Formicidae) in Amazonian clearings - Fowler, H. G. (My University, 1994)
The first case of interference competition through soil dumping in South America is documented between Ectatomma quadridens and Pheidole fallax in Amazonian forest clearings. Workers of the diurnally active E. quadridens arrive at nests of P. fallax at dawn, and begin to fill up nest entrances with soil. During the day, E. quadridens workers remain stationary on the closed nest of P. fallax, and fill soil at the first signs of nest openings. Colonies of P. fallax distant from E. quadridens nests are active for 24 hrs; those near E. quadridens nests are limited for foraging nocturnally after opening nest entrances. This pattern was not found between heterospecific colonies at greater distances from the camp midden, according with the prediction that interference competition is more probable as resources become more concentrated. Colonies of P. fallax near E. quadridens nests located near the camp midden had a net forage intake of 60% of those located in areas without E. quadridens. -Author
Keywords: ant; Hymenoptera; interference competition; soil dumping; Brazil, Amazonia; South America, Amazonia; Ectatomma quadridens; Formicidae; Pheidole fallax